2005
DOI: 10.1136/bjsm.2005.018069
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for anxiety: a systematic review of the research evidence

Abstract: Between March and June 2004, a systematic review was carried out of the research evidence on the effectiveness of yoga for the treatment of anxiety and anxiety disorders. Eight studies were reviewed. They reported positive results, although there were many methodological inadequacies. Owing to the diversity of conditions treated and poor quality of most of the studies, it is not possible to say that yoga is effective in treating anxiety or anxiety disorders in general. However, there are encouraging results, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
270
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(280 citation statements)
references
References 20 publications
5
270
1
4
Order By: Relevance
“…4 Positive results after yoga have been reported in the general population for stress, 25 depression 26 and anxiety. 27 It has also been suggested that simply modifying patterns of improper breathing can lead to significant improvements in psychological symptoms. 28 Yogic breathing is a technique yielding benefits for psychological distress such as stress, anxiety, depression as well as sleep.…”
Section: Introductionmentioning
confidence: 99%
“…4 Positive results after yoga have been reported in the general population for stress, 25 depression 26 and anxiety. 27 It has also been suggested that simply modifying patterns of improper breathing can lead to significant improvements in psychological symptoms. 28 Yogic breathing is a technique yielding benefits for psychological distress such as stress, anxiety, depression as well as sleep.…”
Section: Introductionmentioning
confidence: 99%
“…17 Yoga may also boost confidence and reduce anxiety. [18][19][20] To investigate these benefits, outcome measures are needed that probe objective and subjective qualities of balance if they are to be useful in future clinical settings. Despite yoga's popularity, very few studies have been conducted on the purported benefits of yoga for balance.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicate Asanas increase patient's physical flexibility, strength and coordination while the Pranayama and Meditation practices calm and focus the mind to enhance higher selfawareness and lessen anxiety, that result in better quality of patients life. Some other beneficial and therapeutic effects reported by Yang such as reduction in level of distress, blood pressure, and improvement in mood, resilience and metabolic regulation [9,10]. Studies also indicate yoga is…”
Section: Yoga and Mental Healthmentioning
confidence: 98%